Delineating large‐scale migratory connectivity of reed warblers using integrated multistate models. Issue 1 (28th October 2016) - Procházka, Petr; Hahn, Steffen; Rolland, Simon; van der Jeugd, Henk; Csörgő, Tibor; Jiguet, Frédéric; Mokwa, Tomasz; Liechti, Felix; Vangeluwe, Didier; Korner‐Nievergelt, Fränzi
Abstract: Aim: Assessing the extent of large‐scale migratory connectivity is crucial for understanding the evolution of migratory systems and effective species conservation. It has been, however, difficult to elucidate the annual whereabouts of migratory populations of small animals across the annual cycle. Here, we use the reed warbler ( Acrocephalus scirpaceus ) as one of the most frequently ringed passerines in Europe to demonstrate how ring re‐encounter and geolocator data can be used to effectively quantify range‐wide distribution of different populations. Location: Birds were ringed across Europe and re‐encountered in Europe, Africa and the Middle East. Methods: We employed multistate models which quantify range‐wide distribution of different breeding populations while accounting for the spatial and temporal heterogeneity in the re‐encounter probabilities and differential age‐specific survival during migratory and non‐migratory periods. In addition, we integrated geolocator and breeding abundance data as well as human population density to provide a realistic picture of the year‐round distribution of the reed warbler, a trans‐Saharan migrant. Results: Our modelling approach revealed frequent use of the western Mediterranean flyway for the majority of western European populations, but a higher absolute number of reed warblers used the eastern flyway. Further, many populations used different stopover areas during post‐ and pre‐breeding migration, resulting in an anticlockwise loop migration pattern. Main conclusions: The integrative modelling framework helped us to depict the range‐wide migration pattern more realistically than raw ring re‐encounter data would allow.